A função da história ou a redenção dos oprimidos: inferências das “teses sobre o conceito de história de W. Benjamin” à cultura historiográfica - Santos, Deibson Joaquim dos (2019)
This work is a contribution to the debates about the importance of Walter Benjamin's work for historical knowledge, more specifically, the relevance of the criticism made against the historiographical model inspired by historicism. In addition, let us elaborate arguments that demonstrate his notes for a historiography that promotes historical consciousness in the oppressed class. However, it is necessary to understand that it is not possible to reflect on Benjamin's arguments in the Theses without a dialogue with other texts of his work. Therefore, the central problem is to understand what is the function of history in the perspective of Walter Benjamin. Thus, the hypothesis presented suggests that the writing of History on the optics defended in the ―theses on the concept of history‖ must appropriate the epistemological instruments that oppose the dominant historical and historiographic cultures, especially those based on historicist ideas. . Therefore, it is suggested that there are methodological mechanisms proposed by Walter Benjamin for a historiography that contributes to the redemption of the oppressed. For this, it was necessary to make an interlocution between the Benjaminian writings previous to this text, the reflections elaborated by the commentators and the authors that can contribute to the justification of the persistent arguments in this text. In this sense, it is necessary to understand that the theoretical range of the theses reflects the political, academic praxis and the life of our theorist, so that it would not be possible to construct a work that could reflect on the whole conceptual framework of Benjamin's work through a simple dissertation work. Therefore, efforts had to be made in three perspectives that we identified in the ―Theses on the Concept of History‖: the dominant historiographical and historical culture; historical catastrophe as an instrument for the domination of the oppressed class; the technical reproducibility in the production of historical knowledge and the role of emotions and feeling as an instrument for the redemption of the oppressed and the construction of the historical consciousness of the oppressed. However, these themes will not be dealt with in isolation, since our intention is to justify or ratify the idea that historicist historiography strengthened the instruments of bourgeois domination against the oppressed class, consequently favoring the oblivion of emotions and feelings linked to events. that is, it contributed to dissociate historical processes from the construction of historical consciousness.